Ideological Tensions in Outcome-Based Education: A Philosophical Critique of Arabic Language Curriculum in Islamic Higher Education - Sovia Fahraini; Kamal Yusuf; Muhammad Dhiya' Syaifullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The Outcome-Based Education (OBE) curriculum as a national standard for higher education focuses on measurable achievements and global competencies, but its implementation in Arabic Language Education has the potential to obscure the philosophical, religious, and ideological dimensions of the language of revelation, science, and Islamic civilization. Therefore, this study aims to critique the Arabic Language Education curriculum by examining the suitability of the ideology of Arabic as the language of revelation, science, and Islamic civilization with the technocratic implementation of OBE, and to identify adjustments to remain in line with the vision of Islamic science. This study uses a critical qualitative method with an analysis of the curriculum ideology through a review of OBE documents, interviews with PBA lecturers and students, and a review of philosophical educational literature. The results of the study show four main findings: [1] Philosophical critique of the OBE ideology, [2] Adjustment of the OBE curriculum in Arabic Language Education, [3] Philosophical Dilemmas in the Implementation of OBE, [4] The practical impact of the OBE curriculum on the learning process. This research is expected to harmonize OBE and Arabic language ideology through curriculum design that combines technocratic-pragmatic orientation with philosophical, religious, and ideological dimensions, so that the study program not only meets accreditation standards and global competitiveness but also remains faithful to the mission of Islamic science which is the core spirit of Arabic language education.